2022
DOI: 10.1016/j.addbeh.2021.107092
|View full text |Cite
|
Sign up to set email alerts
|

Getting high to cope with COVID-19: Modelling the associations between cannabis demand, coping motives, and cannabis use and problems

Abstract: During the COVID-19 pandemic, people may use substances like cannabis for enhancement or coping purposes. Behavioral economic demand for a substance is a key determinant of its use and misuse and can be measured via hypothetical purchase tasks. Previous research suggests that motivations to use a substance play a mediational role between elevated substance demand and problems, but comparable mechanistic research has yet to be done in the COVID-19 context and on the effects of cannabis demand on cannabis use pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…The current study provides evidence that indirect exposure to perceived racism-based police use-of-force contributes to past 30-day cannabis use and support extant literature suggesting that Black emerging adult males engage in cannabis use as a form of self-medication to cope with their potentially traumatic experiences ( Leeies et al, 2010 , Vedelago et al, 2022 ).…”
Section: Discussionsupporting
confidence: 79%
“…The current study provides evidence that indirect exposure to perceived racism-based police use-of-force contributes to past 30-day cannabis use and support extant literature suggesting that Black emerging adult males engage in cannabis use as a form of self-medication to cope with their potentially traumatic experiences ( Leeies et al, 2010 , Vedelago et al, 2022 ).…”
Section: Discussionsupporting
confidence: 79%
“…We sought to calculate alpha among the sample which requires variable hypothetical consumption (i.e., consumption beyond free cost). We therefore excluded an additional 17 participants based on this criterion, which is consistent with prior studies utilizing similar purchase tasks (e.g., Vedelago et al, 2022). Further, only four of these 17 participants reported any consumption (0.3, 1.0, 1.0, and 2.0 grams) at free cost suggesting that these 17 excluded participants had no or minimal interest in cannabis use (i.e., negligible RV).…”
Section: Methodsmentioning
confidence: 82%
“…Note that there are studies that question the effectiveness of psychosocial treatments for alcoholism and that describe high relapse rates, with treatment outcomes affected by multiple factors [ 34 , 35 ]. In addition, it is possible that the patients who increased consumption had characteristics typical of addicted patients, such as difficulties in managing craving and other factors similar to the general population that contributed to increased consumption, especially of alcohol, such as using substances as coping strategies or due to boredom [ 36 , 37 ] or because they perceived fewer consequences of drinking more [ 15 ]. These motivational aspects could be integrated as part of the psychological treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, benzodiazepines, cannabis, and tobacco were the substances of which consumption increased the most compared to prior to the pandemic, among patients who previously had an addiction to these substances. A recent study reported that cannabis users who increased cannabis and tend to use cannabis to cope are at increased risk of experiencing negative cannabis-related consequences during the COVID-19 pandemic [ 37 ]. The patients with opioid use disorder were the ones who reported increased use less frequently.…”
Section: Discussionmentioning
confidence: 99%